(untitled) (Semiárida, 2020)
With the aim to evaluate the yields stability of some cultivars of maize in two places of the ecological region VII (General Pico y Santa Rosa), the Official Network of Territorial Trials has been analyzed, according to the methodology proposed by Eberhart and Russell (1966) one variety and six hybrids of maize have been studied in eight different environments. Morgan 400, Cargill Record 120, Dekalb 4F 33 y Morgan Triunfador resulted all superior to the general yield average. Morgan 400 yield overcame the rest. Six cultivars under study can be considered stables in those environments analyzed since their regression coefficients do not differ from the average (b=1). The standard desviation of regression coefficients (S2d) are closed to O. Morgan Triunfador could make a better us of a lower quality environment (b=0,81 y S2d=0).